Penggunaan Bahasa Isyarat Jepang (Shuwa) pada Tokoh Itose Yuki dalam Anime Yubisaki to Renren - Salwa Salsabila; Merri Silvia Basri; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2026)
Abstract: This study is motivated by the importance of examining Japanese sign language (shuwa) as a means of communication for the deaf, as depicted in the popular anime Yubisaki to Renren. This study aims to describe the use of shuwa by the character Itose Yuki in the anime Yubisaki to Renren, specifically in episodes 4–7, and to analyze the meaning of its use in the context of communication using a qualitative descriptive method with a pragmatic analysis, particularly focusing on illocutionary acts. The results of the study indicate the presence of 19 illocutionary acts, comprising 2 assertive illocutionary acts, 6 directive illocutionary acts, 2 commissive illocutionary acts, 6 expressive illocutionary acts, and 3 declarative illocutionary acts. Based on the research results, it is evident that the use of “shuwa” by the character Itose Yuki appears in various communicative situations, whether to convey information, express feelings, or build interpersonal relationships with the interlocutor. Furthermore, Yuki’s use of “shuwa” does not merely function as a communication tool but also serves as a crucial device in character development, reinforcing moral messages, and advancing the plot.